THE ECONOMIC STRUCTURES IN THE ROMANIAN REGIONS AND COUNTIES AND THE EU MEMBER STATES. COMPARATIVE ANALYSES. - Marioara, IORDAN (Strategii Manageriale, 2014)
Bridging the gap between countries, and thus decresing poverty, is the greatest challenge of European countries in the context of the European social cohesion. The risk of future economic difficulties caused by the size of budget deficits is beared by the funds to be allocated to social inclusion in the EU and the EU member countries. They will be concerned in the post-crisis period with aligning the requirements of progress, of poverty reduction, but also of ensuring the sustainability of public finances. For Romania, cohesion is particularly important as most regions show significant differences as compared to the EU average and the national average. This group also includes the South Muntenia Region, which has many advantages for faster progress and to be able to exploit the opportunities offered by the implementation of the Europe 2020 strategy.